Adsorption Site Regulations of [W–O]-Doped CoP Boosting the Hydrazine Oxidation-Coupled Hydrogen Evolution at Elevated Current Density - Meng, Ge; Chang, Ziwei; Zhu, Libo; Chen, Chang; Chen, Yafeng; Tian, Han; Luo, Wenshu; Sun, Wenping; Cui, Xiangzhi; Shi, Jianlin (Nano-Micro Letters, 2023)
Hydrazine oxidation reaction (HzOR) assisted hydrogen evolution reaction (HER) offers a feasible path for low power consumption to hydrogen production. Unfortunately however, the total electrooxidation of hydrazine in anode and the dissociation kinetics of water in cathode are critically depend on the interaction between the reaction intermediates and surface of catalysts, which are still challenging due to the totally different catalytic mechanisms. Herein, the [W–O] group with strong adsorption capacity is introduced into CoP nanoflakes to fabricate bifunctional catalyst, which possesses excellent catalytic performances towards both HER (185.60 mV at 1000 mA cm−2) and HzOR (78.99 mV at 10,00 mA cm−2) with the overall electrolyzer potential of 1.634 V lower than that of the water splitting system at 100 mA cm−2. The introduction of [W–O] groups, working as the adsorption sites for H2O dissociation and N2H4 dehydrogenation, leads to the formation of porous structure on CoP nanoflakes and regulates the electronic structure of Co through the linked O in [W–O] group as well, resultantly boosting the hydrogen production and HzOR. Moreover, a proof-of-concept direct hydrazine fuel cell-powered H2 production system has been assembled, realizing H2 evolution at a rate of 3.53 mmol cm−2 h−1 at room temperature without external electricity supply. Highlights: 1 The [W–O] group with strong adsorption capacity is introduced into CoP to fabricate a bi-functional catalyst towards HER and HzOR. 2 The cell voltage of HzOR coupled electrolyzer with 6W–O–CoP/NF as both anode and cathode catalysts is 1.634 V lower than that of the water splitting system at 100 mA cm−2. 3 A proof-of-concept self-powered H2 production system is assembled to realize the H2 evolution rate of 3.53 mmol cm−2 h−1.